Learning Plan of Moderate Islamic Religious Education in Higher Education - Andika Aprilianto; Muhammad Husnur Rofiq; Akhmad Sirojuddin; Nicky Estu Putu Muchtar; Lusia Mumtahana (LPPM Institut Pesantren KH. Abdul Chalim, 2023)
This article aims to describe and determine the planning of moderate PAI learning at Unisma College and the University of Muhammadiyah Malang. The research method used is qualitative with a case study approach (multi-site design). The results of this article are: The lecturers adhere to the curriculum and syllabus books used to create lecture program units (SAP). Learning planning must include how to implement and evaluate thoroughly and contain moderate Islamic values.